Mercury levels at the UPCD-OP clinic and in biologic samples from exposed individuals - Abalos, Angeline Grace
The World Health Organization (WHO) stated that mercury found in dental amalgam was the greatest source of mercury in the non-industrialized setting. The use of mercury in the dental clinic poses health risks to personnel and patients alike. The aim of this study was to determine the mercury vapor level at the University of the Philippines College of Dentistry, Operative Dentistry clinic (UPCD-OP) and the mercury levels in blood samples gathered from exposed individuals and compare it with recorded occupational safety levels. The air from five sites of the UPCD-OP clinic was drawn through a desiccated filter paper in a cassette attached to an air sampling pump. Blood samples were extracted from ten subjects (five clinicians, four faculty and one personnel). Prior to sampling, a survey questionnaire was distributed to the subjects to determine ether possible sources of mercury exposure. Air and blood samples were brought to laboratories accredited by the Department of Environment and Natural Resources (DENR) and Department of Health (DOH) for analysis. Atomic Absorption Spectrophotometry was used to analyze the air samples while blood samples were analyzed using the Cold Vapor Technique. Answers gathered from the survey questionnaire showed that two subjects were highly exposed to the mercury through occupational exposure, fish consumption, use of hair dyes and presence of amalgam restorations in their oral cavity. Laboratory analysis showed that the mercury vapor level in the UPCD-OP Clinic ranged from <0.0055 pg/m3- 0.2727 pg/m3. These levels are below the Department of Labor and Employment's (DOLE) Threshold Limit Value recommendation, which is 50 pg/m3. Results from the analysis of blood samples collected from the exposed individuals showed that mercury levels was 0.1 microgram per deciliter (pg/dL) for all subjects, which is below the biological exposure index of 150 pg/dL advised by Occupational Safety and Health Administration (OSHA). The results of this study show that the mercury vapor level at the UPCD-OP Clinic and mercury level in bioloqical samples are within the current health standards.